Sonification and Music: Science meets Art. Issue 1 (2nd January 2021) - Devroop, Chatradari 'Chats'; Titlestad, Michael
Abstract : The opposites, science and the arts, have always enjoyed a relationship. Recently, this relationship has been expressed in sonification, a branch of science seeking to add sound to data, giving data music-like intelligibility. Scientists believe that our aural capabilities are a potentially rich source of data that could assist in problem solving. In 2020, a sonic realization of the coronavirus was generated using its spike protein data. This sonification endeavoured to probe the coronavirus aurally. However, the creators of this sonified scientific probe are now claiming that their experiment is also a music composition. We examine this claim. This paper is underpinned by the conviction that not all sound is music. Music cannot represent anything other than itself because our understanding of music is always via allegory. Therefore, the efforts of Buehler, it is argued, are misdirected and trivial when placed in the stressed socio-political context of COVID-19.